2019
DOI: 10.5539/mas.v13n10p60
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Mapping of Soil Properties for Precision Agriculture Using Geographic Information System (GIS) Based Geostatistics Models

Abstract: In precision Agriculture, geostatistical methods as a predictive tool have been extensively utilized. The approach estimates soil properties spatial variability and dependency. This study was carried out in Ovia north east Local Government Area of Edo State of Nigeria in order to map soil properties (Sand, Clay, pH, OC, P, N and CEC) and redict their spatial variability. Twenty-nine (29) soil samples were collected randomly from Typic Kandiudults soil type under three different land use, teak forest plantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Based on these, a series of quantitative indicators were used to discuss the forecast results of different models. That was an innovative attempt in the thinking of plant nutrients in soil analysis because of many studies focus only on one method in the past [6,9,10,13]. The results showed that TN is moderately enriched and AP is deficient in the study area, which was consistent with the geochemical survey results.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Based on these, a series of quantitative indicators were used to discuss the forecast results of different models. That was an innovative attempt in the thinking of plant nutrients in soil analysis because of many studies focus only on one method in the past [6,9,10,13]. The results showed that TN is moderately enriched and AP is deficient in the study area, which was consistent with the geochemical survey results.…”
Section: Discussionsupporting
confidence: 82%
“…Spatial variation is generally divided into intrinsic variation and extrinsic variation. Internal changes are caused by structural factors, while external changes are caused by random factors [6,10,33]. The structural factors of internal change include soil texture, soil particle, soil bulk density, etc.…”
Section: Ordinary Kriging Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, experimental data were recorded and analyzed for required objectives that to determine and to present fine-grained soil behaviors of the town. Laboratory results were mapped to have spatial information on the foundation material/soil using ArcGIS software (18,19) .…”
Section: Methodsmentioning
confidence: 99%